SULFUR SPECIATION IN KEROGENS OF THE ORBAGNOUX DEPOSIT (UPPER KIMMERIDGIAN, JURA) BY XANES SPECTROSCOPY AND PYROLYSIS - Sarret G.; Mongenot T.; Connan J.; Derenne S.; Kasrai M.; Michael Bancroft G.; Largeau C. (My University, 2002)
Thermally immature, extremely sulfur-rich kerogens from the Orbagnoux deposit have been extensively studied over the last few years for their chemical structure, source organisms and depositional conditions. However, important uncertainties remain concerning sulfur speciation in these kerogens and changes in sulfur functionality that occur upon thermal stress. In the present study sulfur speciation for isolated kerogens from the five facies recognized in the deposit was established via K- and L-edge X-ray Absorption Near Edge Structure (XANES) spectroscopy. A representative sample of the most organic-rich facies of the deposit, the dark parallel laminae, was examined by ''direct'' pyrolysis at 400 °C and the results compared with those previously derived from ''indirect'' pyrolysis (carried out under the same conditions but from kerogen pre-heated at 300 °C). XANES examination was performed on the unheated kerogen, the pre-heated kerogen, the insoluble pyrolysis residues and the effluents obtained via these two pyrolyses. Sulphur distribution was also determined via elemental analyses and measurements of evolved H2S. Identification of the pyrolysis products of the ''direct'' experiment was performed by gas chromatographic/mass spectrometric analyses, before and after desulfurization, of the crude pyrolysate and of separated fractions and sub-fractions. Substantial quantitative and qualitative differences are thus noted between the ''direct'' and ''indirect'' pyrolyses at 400 °C, as a result of the cleavage and aromatization of some sulfide bridges occurring upon pre-heating at 300 °C. Thus, the ''indirect'' pyrolysis appears somewhat less efficient for the thermal cracking of the macromolecular structure of the kerogen. Nevertheless, it provides more detailed information on the intermolecularly sulfur-linked carbon skeletons that build up the bulk of this structure owing to (i) the release of OSC with higher carbon numbers and (ii) the much easier desulfurization of the molecular aggregates probably due to a lower degree of cross-linking. XANES spectroscopy showed that (i) thiophenes are the main sulfur species in the unheated kerogens and (ii) substantial aromatization of the non-thiophenic sulfur forms occurs upon the thermal treatments.
Keywords: Kimmeridgian; Mesozoic::Jurassic::Upper::Kimmeridgian; Мезозой::Юрская::Верхний::Киммериджский